The study of relationship between religious orientations with emotional intelligence components Among Students of Shahid Beheshti University of Medical Sciences - Tajabadi, Reza (Archives of Advances in Biosciences, 2017)
Background and Objectives: Religious orientation is one of the factors influencing behavior and cognition.Considering the necessity of recognizing the factors affecting students' religious orientation, the present study has investigated the relationship between religious orientation and emotional intelligence components in students of Shahid Beheshti University of Medical Sciences. Materials and Methods : The design of this research is descriptive-correlational. The statistical population consisted of all medical students of Shahid Beheshti University of Medical Sciences. In this study, a sample size of 63 students were studying (girls = 32, boys = 31 ), who were selected by random sampling. In the present study, the confidentiality and all ethical principles are observed. Also, the authors of the article have not reported any conflicts of interest. The tool for collecting information was Alport Religious Orientation Questionnaire and Bar-An Emotional Intelligence Questionnaire. Data were analyzed using SPSS software and descriptive statistical methods (mean and standard deviation) and regression analysis. Result: The findings of this study indicate that external and internal religious orientation has a significant effect on the components of emotional intelligence at 5% level.The value of this coefficient in this research is 0.19, in fact, students' religious orientation has 19% ability to predict the components of emotional intelligence. Conclusion: The results of this study showed that religious orientation can play an effective role in predicting students' emotional intelligence.Students with a high religious orientation are flexible, tolerant of stress and high happiness. They have a high responsibility in social situations.